2021
DOI: 10.1088/1755-1315/747/1/012111
|View full text |Cite
|
Sign up to set email alerts
|

The development of textbook based on brain-based learning (BBL) in material organization system of life for the junior high school science

Abstract: This study aims to develop textbooks on Brain-Based Learning in Materials Organization of Life for the Junior High School. 92.8% of 70 students from Tenth Junior High School said need an interesting picture book, 92.8% of 70 students require illustrative images that support the material, and 89.9% said need a book that helps remember long-term. The purpose of this study is to obtain a development process and textbook based on Brain-Based Learning (BBL) that Effectiveness for The Students Junior High School in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 9 publications
0
4
0
1
Order By: Relevance
“…This activity helps students inquire and give an impression about the concept of the lesson that has been received. Learning that gives the impression can positively improve retention (Kusumaningrum et al, 2021). Celebrations build positive responses that help construct students' memory of the concepts studied (DeSipio et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…This activity helps students inquire and give an impression about the concept of the lesson that has been received. Learning that gives the impression can positively improve retention (Kusumaningrum et al, 2021). Celebrations build positive responses that help construct students' memory of the concepts studied (DeSipio et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Fig 3 also shows that 16% of the studies on BBL centred on science (four studies). These included those of Al-Balushi and Al-Balushi (2018), which was conducted in Muscat, and of Kusumaningrum et al (2021), Willis (2007), andYasar (2017). 12% of the studies focused on biology classrooms (three studies), namely those by Varghese and Pandya (2016), Akyürek and Afacan (2013) and Aydin and Yel (2011).…”
Section: Discussionmentioning
confidence: 99%
“…Apart from the usage of mnemonic technique in mathematics learning, numerous studies have also employed the technique in other subjects. Kusumaningrum et al (2021) employed mnemonic method in developing textbook based on brain-based learning. The results showed that the learning outcome of students has increased.…”
Section: Literature Reviewmentioning
confidence: 99%